Nurturing the Earth through Islamic Ethical Practices and Community-Based Permaculture in Indonesia - Ummi Hanik Esaputri; Nada Nadhifa; Hanif Budiman; Putu Ayu Pramanasari Agustiananda (Jurnal Sosiologi Reflektif, 2025)
The global environmental crisis, marked by climate change, deforestation, and ecosystem degradation, has brought widespread social impacts, including economic inequality, health crises, and food insecurity. In Indonesia, environmental pressures have intensified due to unsustainable agricultural practices, rapid urbanization, and extractive industries, necessitating new development models that prioritize environmental regeneration and social resilience. This study aims to explore how Islamic ecological principles are operationalized through permaculture practices at the Bumi Langit Institute and Kedai Teh Umran in Yogyakarta. This research employed a qualitative method with an interpretive approach. Data were collected through semi-structured interviews, participant observation, and document analysis conducted at both research sites. The data were then analyzed using thematic analysis techniques based on Groat and Wang’s six-phase framework. The findings reveal that the principles of khilafah (stewardship), barakah (blessing), and mizan (balance) have been effectively embodied in agroforestry systems, waste-to-resource cycles, and community development initiatives grounded in Islamic ethics. The study implies that faith-based and community actors play a vital role in addressing contemporary ecological crises and highlights the need for stronger partnerships between religious institutions, academic bodies, and environmental practitioners to advance spiritually grounded innovations in the Anthropocene era.  Krisis lingkungan global yang ditandai oleh perubahan iklim, deforestasi, dan degradasi ekosistem telah membawa dampak sosial yang luas, termasuk ketidaksetaraan ekonomi, krisis kesehatan, dan kerawanan pangan. Di Indonesia, tekanan lingkungan semakin meningkat akibat praktik pertanian tidak berkelanjutan, urbanisasi cepat, dan industri ekstraktif, sehingga diperlukan model pembangunan baru yang berfokus pada regenerasi lingkungan dan ketahanan sosial. Penelitian ini bertujuan untuk mengeksplorasi bagaimana prinsip-prinsip ekologi Islam dioperasionalkan melalui praktik permakultur di Bumi Langit Institute dan Kedai Teh Umran di Yogyakarta. Penelitian ini menggunakan metode kualitatif dengan pendekatan interpretatif. Data dikumpulkan melalui wawancara semi-terstruktur, observasi partisipatif, dan analisis dokumen di Bumi Langit Institute dan Kedai Teh Umran. Analisis data dilakukan dengan teknik analisis tematik berdasarkan kerangka enam fase Groat dan Wang. Temuan penelitian menunjukkan bahwa prinsip khilafah, keberkahan (barakah), dan keseimbangan (mizan) telah berhasil diwujudkan dalam sistem agroforestri, siklus limbah, dan pengembangan komunitas berbasis etika Islam. Implikasi penelitian ini menegaskan bahwa aktor berbasis agama dan komunitas memiliki peran vital dalam mengatasi krisis ekologi kontemporer, serta mendorong perlunya kemitraan antara lembaga keagamaan, akademisi, dan praktisi lingkungan untuk memperkuat inovasi berbasis nilai spiritual di era Antroposen.